ENHANCING QUALITY OF LIFE THROUGH EVIDENCE-BASED REHABILITATION INTERVENTIONS IN A MULTIFACETED APPROACH. - ‏Hamad Mesfer Mansor Al Sawidan, Mohammed Masfer M Al Sawydan, Hussain Hassan H Al Murdif, Faisal Mohsen Abdalluh Alorif, Hassan Yahya Mohammed Moafa, Hamad Dhafer Ali Al Obaya, Fahad Ahmed Mahdi Alharthi, GalebAbdullehhusseinalfageer, Mohammed Ahmed Sale (Chelonian Research Foundation, 2023)
In order to improve the quality of life, this article addresses numerous perspectives of evidence-based helpful intercessions. Through an amalgamation of existing writing and talk of strategies and comes about, it illustrates the imperative part of collective procedures in standard returns. This article combines proof from different sources to highlight the interaction of therapeutic mediation and its effect on general well-being. This investigation comes about in proposals that will directly hone and investigate this vital range. Through this exertion, this article centers on the progressing talk concerning recovery to progress a person's quality of life. Keywords: Quality of life, Evidence-based, Rehabilitation interventions, Multifaceted approach